Biomechanical properties of ascending aortic aneurysms: Quantification of inter- and intra-patient variability - Sigaeva, Taisiya; Sattari, Samaneh; Polzer, Stanislav; Appoo, Jehangir J; Di Martino, Elena S (Journal of biomechanics, 2021)
This study investigates the biomechanical properties of ascending aortic aneurysms focusing on the inter-patient differences vs. the heterogeneity within a patient's aneurysm. Each specimen was tested on a biaxial testing device and the resulting stress-strain response was fitted to a four-parameter Fung constitutive model. We postulate that the inter-patient variability (differences between patients) blurs possible intra-patient variability (regional heterogeneity) and, thus, that both effects must be considered to shed light on the role of heterogeneity in aneurysm progression. We propose, demonstrate, and discuss two techniques to assess differences by, first, comparing conventional biomechanical properties and, second, the overall constitutive response. Results show that both inter- and intra-patient variability contribute to errors when using population averaged models to fit individual tissue behaviour. When inter-patient variability was accounted for and its effects excluded, intra-patient heterogeneity could be assessed, showing a wide degree of heterogeneity at the individual patient level. Furthermore, the right lateral region (from the patient's perspective) appeared different (stiffer) than the other regions. We posit that this heterogeneity could be a consequence of maladaptive remodelling due to altered loading conditions that hastens microstructural changes naturally occurring with age. Further validation of these results should be sought from a larger cohort study.
Keywords: Fung model; Aneurysms; Aortic Aneurysm; Stress, Mechanical; Intra-patient variability; Tangent moduli; Regional variability; lidé; Ascending thoracic aorta; Inter-patient variability; Aortic Aneurysm, Thoracic; aortální aneurysma; Cohort Studies; kohortové studie; aneurysma hrudní aorty; mechanický stres; Humans; Biaxial testing; Circumferential regions